1971
DOI: 10.1177/001872087101300204
|View full text |Cite
|
Sign up to set email alerts
|

The Adult Human Hand: Some Anthropometric and Biomechanical Considerations

Abstract: Recent studies of the anthropometry and selected biomechanical characteristics of hands are summarized. These include: ( I ) conventional anthropometry of male and female hands, (2) the anthropometry of the relaxed hand, (3) comparison of certain engineering anthropometric and performance parameters between bare and pressure-gloved hands, and (4) the ability to retain grips on selected handles under high dynamic loads. The utility of these data for human factors engineering is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
2

Year Published

1980
1980
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(69 citation statements)
references
References 6 publications
1
66
0
2
Order By: Relevance
“…selected biomechanical characteristics of hands are summarized in a journal article by Garrett (1971),11 These include: (1) conventional anthropometry of male and female hands, (2) the anthropometry of the relaxed hand, (3) comparison of certain engineering, anthropometric and performance parameters between bare and pressure-gloved hands, and (4) the ability to retain grips on selected handles under high dynamic loads. The utility of these data for human factors engineering is discussed.…”
Section: A Review Of Some Literature On the Handmentioning
confidence: 99%
“…selected biomechanical characteristics of hands are summarized in a journal article by Garrett (1971),11 These include: (1) conventional anthropometry of male and female hands, (2) the anthropometry of the relaxed hand, (3) comparison of certain engineering, anthropometric and performance parameters between bare and pressure-gloved hands, and (4) the ability to retain grips on selected handles under high dynamic loads. The utility of these data for human factors engineering is discussed.…”
Section: A Review Of Some Literature On the Handmentioning
confidence: 99%
“…Studies by earlier scholars primarily focused on the body measurement related to the grip force of hands (Kitagawa and Miyashita, 1978;Miyatake et al, 2000;McGorry, 2001;Hulens et al, 2001;Rolland et al, 2004;Fogelholm et al, 2006;Wu et al, 2009;Cavuoto and Nussbaum, 2013). Garrett (1971) conducted the measurements aimed at the measurement model of hands by means of conventional tools. Garmer et al (2002) and Kwon et al (2009) subsequently conducted the correction of hand measuring technology.…”
Section: Theories Of Space Allocationmentioning
confidence: 99%
“…Yu et al (2013) proposed to conduct accurate measurements of hand dimensions using 2D and 3D methods. For custom-made gloves, direct measurement tools, such as flexible measuring tape, calipers, measuring boards, and rulers, are traditionally used to obtain hand dimensions for glove design and pattern development (Garrett, 1971). Yu et al (2013) reported that the objective of the present study is to propose a new approach of obtaining hand anthropometric measurements using 2D and/or 3D image analyses and comparing the new method with the conventional direct measurement method.…”
Section: Theories Of Space Allocationmentioning
confidence: 99%
“…Generell werden Objekte als schön empfunden, wenn diese Harmonie, Proportion und Klarheit vereinigen [20]. Drei unterschiedliche Handtypen, basierend auf Kretschmer, sind bekannt: F der ektomorphe Typ mit langen, schlanken Händen, F der athletische Typ mit breiteren, aber sehr gut proportionierten Händen sowie F der pyknische Typ mit kurzen Fingern und einem breiten Handrücken ( [9]; . Abb.…”
Section: Idealästhetik Der Handunclassified